Albumin-globulin ratio: a novel predictor of sepsis after flexible ureteroscopy in patients with solitary proximal ureteral stones - Lu, Junlin (Transl Androl Urol, 2020)
BACKGROUND: To identify predictors of sepsis after flexible ureteroscopy (fURS) in patients with unilateral, solitary, proximal ureteral stones and evaluate the association between albumin-globulin ratio (AGR) and sepsis. METHODS: Overall, 759 patients who underwent fURS were retrospectively enrolled. Univariate and multivariate logistic regression analyses were performed to identify predictors of sepsis after fURS in patients with solitary proximal ureteral stones. Then A nomogram was generated using the predictors. RESULTS: Sepsis occurred in 43 patients (5.7%), and 6 (0.8%) of them developed septic shock. Univariate analysis showed that age, female sex, albumin concentration, globulin concentration, AGR, pre-operative fever, white blood cell (WBC) count, urine culture (UC) result, urine WBC count, and urine nitrite result were predictors of sepsis. Multivariate analysis identified AGR <1.2 [odds ratio (OR) =2.810, 95% confidence interval (CI): 1.245–6.342, P=0.013] and positive UC (OR =10.520, 95% CI: 4.489–24.653, P<0.001) as independent predictors. When AGR <1.2 and positive UC were combined, area under the receiver operator characteristic curve was 0.825. Then patients were categorized by different AGR level (“≥1.4”, “1.2–1.4”, “1.0–1.2”, “<1.0”), and corresponding sepsis rates were 27.7%, 9.8%, 4.5% and 2.5%. CONCLUSIONS: Positive UC and low AGR were independent predictors of post-fURS sepsis. Cautious pre-operative evaluation and optimized treatment strategy should be considered to minimize infectious complications.